World Bank Lending and the Quality of Economic Policy. Issue 1 (2nd January 2016) - Smets, Lodewijk; Knack, Stephen
Abstract: This study investigates the impact of World Bank development policy lending on the quality of economic policy. It finds that the quality of policy increases, but at a diminishing rate, with the cumulative number of policy loans. Similar results hold for the cumulative number of conditions attached to policy loans, although quadratic specifications indicate that additional conditions may even reduce the quality of policy beyond some point. The paper measures the quality of economic policy using the World Bank's Country Policy and Institutional Assessments of macro, debt, fiscal, and structural policies, and considers only policy loans targeted at improvements in those areas. Previous studies finding weaker effects of policy lending on macro stability have failed to distinguish loans primarily intended to improve economic policy from other loans targeted at improvements in sector policies or in public management. The paper also shows that investing in economic policy does not 'crowd out' policy improvements in other areas, such as public sector governance or human development. The results are robust to using alternative indicators of policy quality and correcting for endogeneity with system generalized methods of moments and cross-sectional two-stage least squares. The more positive results in the study relative to some previous studies are consistent with claims by the World Bank that it has learned from its mistakes with traditional adjustment lending.